La presencia de la lengua inglesa en carteles publicitarios en las calles de Las Palmas de Gran Canaria - Carmen Isabel Luján García (Miscelánea: A Journal of English and American Studies, 2010)
This paper intends to offer an analysis of the outstanding presence of the English language in our everyday life. English has become a very fashionable language in our culture, and we will provide evidence of this fact. With that purpose in mind, we have focused this research on the analysis of the noticeable number of shop signs with English words that can be seen in the two most important shopping areas of Las Palmas de Gran Canaria. The sample is composed of 132 shop signs in the area of Triana, and 80 signs in the area of Mesa y López. We have distinguished different kinds of uses of the English language in shop signs (English words and Genitive Construction, English/Spanish words and hybrids-mixture of English and Spanish in the same word). The study also sheds light on the different kinds of shops associated with the use of English words. Fashion and communication shops, along with restaurants, are the ones that use English words and expressions most frequently. As regards the preference for British or American English, no variety seems to be preferred over the other.
Keywords: English; shop signs; streets; Las Palmas de Gran Canaria; advertising